Boron–Based Electrolytes for Rechargeable Magnesium Batteries: Biography and Perspective. Issue 9 (18th August 2022) - Ren, Wen; Cheng, Mingxiang; Wang, Yaru; Zhang, Duo; Yang, Yang; Yang, Jun; Wang, Jiulin; NuLi, Yanna
Abstract: Rechargeable magnesium batteries (RMBs) are a promising alternative in the post–lithium era for their high volumetric capacity, crustal abundance, and metallic safety. Electrolytes for RMBs have experienced a development process from the initial Grignard compound to today's diversified single magnesium salt. Among them, the boron‐based electrolyte plays a significant connecting link between the preceding and the following. This review retrospectively combed the origin and development course of boron–magnesium electrolyte and focuses on the application of three representatives: borohydride, boron‐center fluorinated alkoxylate, and closo–borane cluster. Fundamental understandings and typical concerns correlative with the Mg−B electrolyte designs are highlighted and briefly discussed. Finally, future direction and possible proposals for practical Mg−B electrolytes are put forward. Abstract : All about Mg−B electrolyte : The review aims at a systematic retrospection on the biography of Mg−B electrolytes, and the practicability analysis of three representatives is described.